Effects of ozonation on disinfection by-product formation potentials and biostability in a pilot-scale drinking water treatment plant with micro-polluted water. Issue 20 (6th September 2021) - Gao, Huan; Ji, Hongjun; Yu, Ran; Zhu, Guangcan
ABSTRACT: The accelerated urbanization in China has caused intensified micro-pollution problems for drinking water sources, severely challenging drinking water treatment efficiencies and its biostability. This study mainly investigated the effects of ozonation on disinfection by-product formation potentials (DBPFPs) and biological dissolved organic carbon (BDOC) in a pilot-scale ozonation-biological activated carbon advanced drinking water treatment plant with micro-polluted raw water. The results indicated that the micro-polluted water would be effectively treated in the advanced treatment processes with DBPFPs significantly eliminated. The total removal rates of trihalomethane formation potentials (THMFPs) and haloacetic acid formation potentials (HAAFPs) increased with the elevated ozone dosage to finally a relatively stable stage, and the maximum removal rates of 77.3% and 57.0%, respectively, were achieved at the ozone dosage of 2 mg/L. The bromine incorporation in total THMFPs (TTHMFPs) was dramatically suppressed after integrated advanced treatment processes, while that in total HAAFPs (THAAFPs) was promoted with the corresponding increment of up to 25.3% for bromine incorporation factor, which caused relatively high brominated HAAFP proportions in the treated water than in the raw water. In addition, the BDOC generation rate and THAAFP removal rate during the post-ozonation treatment displayed apparent positive correlation, and a similar relationship was observed for the BDOC degradation rate and TTHMFP removal rate during the BAC treatment in the studied ozone dosage (1 ∼ 5 mg/L). The findings strongly implied a promising alternative to measure DBPFP removal rate instead of BDOC level for more sensitive and convenient monitoring of the biostability in the reclaimed water. GRAPHICAL ABSTRACT: UF0001